Household Resource Allocation in Stepfamilies: Darwin Reflects on the Plight of Cinderella - Case, Anne; Lin, I-Fen; McLanahan, Sara (American Economic Review, 1999)
Household Resource Allocation in Stepfamilies: Darwin Reflects on the Plight of Cinderella by Anne Case, I-Fen Lin and Sara McLanahan. Published in volume 89, issue 2, pages 234-238 of American Economic Review, May 1999